PENGARUH DISTRIBUSI DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK UNICHARM DARI PT. NIRMALA PANGAN SEJAHTERA KE INDOGROSIR - Indri Astuti; Usran Masahere (CV Edujavare Publishing, 2024)
This study aims to delve deeper into how distribution and promotion affect the purchasing decision of a particular product, namely Unicharm products, from the perspective of PT. Nirmala Pangan Sejahtera as the main distributor to Indogrosir as the main customer. Data for this study was collected through questionnaires distributed to 30 purchasing staff at Indogrosir, allowing researchers to gain a comprehensive insight into perceptions and purchasing preferences from the customer's point of view. Data analysis was performed using multiple linear regression analysis and multiple correlation tests. The analysis results indicate that distribution has a significant impact on purchase decisions, with a t-value of 2.150 (t- t-table 2.042) and a significance level of 0.041 (<0.05), leading to the rejection of Ho1 and acceptance of Ha1. Promotion also has a significant impact, with a t-value of 2.902 (t-table 2.042) and a significance level of 0.007 (<0.05), resulting in the rejection of Ho2 and acceptance of Ha2. The F-test indicates that distribution and promotion jointly have a significant effect on purchase decisions, with an F-value of 9.366 (F-table 4.20) and a significance level of 0.001 (<0.05). The simultaneous R² value of 0.410 indicates that 41% of the variation in purchase decisions is explained by distribution and promotion, while other variables explain the remaining 59%. Distributors such as PT Nirmala Pangan Sejahtera must deeply understand how their distribution and promotion strategies can influence their customers' purchasing decisions and how they can continue to improve their performance in this regard to remain competitive in an increasingly fierce market.